Governing through lifestyle—Lalonde and the biopolitical management of public health in Canada - Foth, Thomas (Nursing philosophy, 2018)
In 1974, the Liberal government of Pierre Trudeau released a "green paper" known as the Lalonde Report, after the health minister at that time. The report formulated perspectives on health and the main concepts and ideas developed in it, particularly the concept of "lifestyle," which became the foundation of public health policies in many different European countries and the United States. The concept of "lifestyle" connected personal behaviour and habits to the individual health condition; people were not dying due to a lack of access to medical care but because they lived a life prone to personal risk taking. Furthermore, what is seldom discussed is that this report not only propagated the (neo)liberal view of citizens as autonomous rational actors (homo oeconomicus), with personal responsibility for their health, but it was a first step in the transformation of Medicare and went far beyond the question of health promotion. Health was no longer something that happened to a person but was created through personal choice and, therefore, one had to assume responsibility for one's behaviour. Using Foucault's definition of government as the "conduct of conduct," we will demonstrate that the Lalonde report must be understood as a specific "technology of government" and contributed to a neoliberal transformation of health care despite the fact that the Canadian system of Medicare was based on the idea of universality, meaning citizens had equal access to health care independent of their socio-economic situation. As we will demonstrate, the Lalonde report undermined this foundation and initiated a profound reorientation, not only of the healthcare system, but even more importantly, it radically changed the way we think about our behaviour around health-related issues. We will also discuss how the making of the report contributed to the redefinition of politics and demonstrated a lack of concern with liberal-democratic decision-making processes.